Bringing Personalized Medicine to a PACT Program: A Quality Improvement Project. (January 2020) - Conley, Virginia M.; Daack-Hirsch, Sandra; Halbmaier, Katie; Shaw, Lisa
INTRODUCTION: Programs for assertive community treatment (PACT) serve persons with severe mental illness who have been unsuccessful with traditional outpatient services. Many PACT clients struggle to obtain symptom relief with medications that often have poor efficacy and undesired side effects, which can result in nonadherence, relapse, and increased health care utilization with associated costs.AIMS: This quality improvement project aimed to improve client and PACT program outcomes by incorporating pharmacogenomic testing into the psychopharmacological decision-making process.METHODS: The project used a pre–posttest design with each client serving as their own control to evaluate changes in clients' symptoms and program outcomes resulting from pharmacogenomics-guided medication management.RESULTS: Following project implementation, clients' symptoms were decreased and both engagement in care and stability in the community increased. Psychiatric hospitalizations and associated costs decreased.CONCLUSIONS: This project suggests utility for using pharmacogenomics testing to personalize care for persons with severe mental illness.